Prenatal Diagnosis of Single Umbilical Artery: Incidence, Counselling and Management in Indian Scenario - Shah, Nupur (J Obstet Gynaecol India, 2018)
PURPOSE: The objective of this study is to report the incidence of single umbilical artery (SUA) on prenatal diagnosis and formulate protocol for counselling and its management in Indian scenario. METHOD: A total of 1024 cases were screened for Single umbilical artery (SUA) between 12 and 20 weeks gestation during the 1 year period from May 2016 to April 2017. Targeted anomaly scan was performed for all cases at 18–20 weeks. Those with additional structural anomalies were subjected to invasive genetic testing. Serial growth monitoring starting from 28 weeks was done. RESULTS: Out of ten cases diagnosed with SUA, five had isolated SUA. Two out of five cases of isolated SUA developed FGR in third trimester. Out of the remaining, three cases with additional structural anomalies had normal foetal karyotype, whereas other two cases showed chromosomal abnormalities (12pder and trisomy 18). CONCLUSION: Targeted anomaly scan is must in all cases of SUA. Invasive genetic testing must be offered in case of associated anomalies. Serial growth monitoring in third trimester is an important part of protocol.